PENGARUH KOMPETENSI DAN PROFESIONALISME TERHADAP KINERJA PEGAWAI DENGAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MEDIASI PADA PEGAWAI DINAS PERHUBUNGAN KOTA SURABAYA BIDANG PRASARANA TRANSPORTASI - Gugo, Hilmy (MANAJEMEN DEWANTARA, 2023)
Apparatus resources have an important role in developing government order. where the driving force of government organizations are humans or employees who work within the framework of their duties, functions and responsibilities. The problem that will be researched is the Influence of Competency and Professionalism on Employee Performance with Information Technology as a Mediating Variable for Surabaya City Transportation Service Employees in the Transportation Infrastructure Sector. This research will use quantitative research methods and measure the influence between variables, namely trying to measure the influence of the Competency and Professionalism variables on Employee Performance with Information Technology as a Mediating Variable for Surabaya City Transportation Service Employees in the Transportation Infrastructure Sector. The results of research by testing that competency variables on the performance of Surabaya City Transportation Service employees in the Transportation Infrastructure Sector, this is proven by a p-value of 0.005. In testing the professionalism variable on the performance of Surabaya City Transportation Service employees in the Transportation Infrastructure Sector, this was proven by a p-value of 0.009. In testing the competency variable for information technology employees of the Surabaya City Transportation Agency in the Transportation Infrastructure Sector, this was proven by a p-value of 0.000, testing the professionalism variable for information technology employees of the Surabaya City Transportation Agency in the Transportation Infrastructure Sector, this was proven by a p-value of 0.009 And in testing the information technology variable on the performance of Surabaya City Transportation Department employees in the Transportation Infrastructure Sector, this was proven by a p-value of 0.002